2020
DOI: 10.26719/emhj.20.012
|View full text |Cite
|
Sign up to set email alerts
|

Predicted 10-year risk of cardiovascular disease in the Islamic Republic of Iran and the body mass index paradox

Abstract: Background: Assessment of the risk of cardiovascular disease is essential for disease prevention in every region. Aims: This study aimed to investigate the 10-year risk of cardiovascular disease and its determinants in an adult population in Shahroud, Islamic Republic of Iran. Methods: A total of 4737 people aged 45-69 years were evaluated. The 10-year risk of cardiovascular disease was calculated using the Framingham risk scoring method. Cardiovascular disease risk is reported as per cent risk and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Metabolic syndrome (MS) refers to a group of many disorders such as insulin resistance, dyslipidemia, inflammation, hypertension, obesity, and hepatic steatosis (Moller & Kaufman, 2005). It was reported that 9.9% of North Indians men and 42% of Iranian women are at risk for the disease which is identified as a threat to the health of the community (Emamian et al., 2020). The prevalence of MS is high in developed countries and is rising in developing countries (Saklayen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MS) refers to a group of many disorders such as insulin resistance, dyslipidemia, inflammation, hypertension, obesity, and hepatic steatosis (Moller & Kaufman, 2005). It was reported that 9.9% of North Indians men and 42% of Iranian women are at risk for the disease which is identified as a threat to the health of the community (Emamian et al., 2020). The prevalence of MS is high in developed countries and is rising in developing countries (Saklayen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3 The mean 10-year risk of developing CVD in Iran was 16.4%, and 28.3% of the participants had a risk of more than 20% (47.8% of the men and 14.9% of the women). 4 Non-modifiable risk factors include age, gender, genetics, and family history; modifiable risk factors include smoking, diet, alcohol consumption, and physical inactivity. 5 Hypertension is well recognised as a global health issue.…”
Section: Introductionmentioning
confidence: 99%
“…The FRS algorithm considers multiple sex-specific risk factors such as age, systolic blood pressure (SBP), total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), smoking habit, diabetes status and antihypertensive medication treatment 5. This valuable CVD risk prediction model has been widely used in both developed and developing countries 7. The FRS can improve the quality of care for hypertensive patients and ultimately help reduce the CVD burden.…”
Section: Introductionmentioning
confidence: 99%